BASE-6 psychological adjustment scale validation in the context of Indonesian adolescents - Ersa Lanang Sanjaya; Reynalda Fildzah Dessyrianti; Fibia Tista Avanti (Institut Agama Islam Negeri Langsa, 2025)
This study aimed to adapt and validate the Brief Adjustment Scale–6 (BASE-6) for use among Indonesian adolescents. Psychological adjustment plays a critical role in adolescent development, making it essential to establish a culturally relevant and age-appropriate assessment tool. The BASE-6, a brief yet robust measure of psychological adjustment, was selected for adaptation. Confirmatory factor analysis demonstrated strong construct validity, with model fit indices, including the Comparative Fit Index (CFI), Tucker–Lewis Index (TLI), Root Mean Square Error of Approximation (RMSEA), and Standardized Root Mean Square Residual (SRMR), collectively indicating a well-fitting model for the Indonesian context. The findings support the suitability of the adapted BASE-6 for assessing psychological adjustment in the Indonesian adolescent population. This validated instrument is expected to contribute to future research and inform interventions designed to promote adolescent mental health.